Commercial equine production in New Zealand 4: welfare implications of the New Zealand production systems - Rogers CW; Legg K; Gibson M; Gee EK (CSIRO Publishing, 2023)
From racehorses to family pets, equine production and management is primarily pasture-based in New Zealand. Pasture-based equine production systems largely reflect the horse’s ecological niche and have a unique set of management and welfare challenges. This review examines the potential welfare issues related to the management of horses in New Zealand. The economic value of horses varies greatly depending on their usage, which covers a wide spectrum from pest species (e.g. feral horses) to production (e.g. racehorses) and companion animals (e.g. leisure and sport horses). The view of where the horse is positioned on this spectrum may cause differing welfare threats to horses, due to the economic considerations, which drive the majority of welfare and managemental decisions. The organisation, management, racing and wastage metrics of the Thoroughbred racehorse industry are well documented, and the benefits of the pasture-based system have become evident through less stressful weaning practices and opportunity for early exercise (which has been associated with longer careers and fewer musculoskeletal injuries). Identification of equine-welfare research priorities in New Zealand remains challenging, given the lack of vertical integration of many sectors of the equine industry resulting in fragmented and limited availability of data.
Keywords: agricultural systems; animal behavior; animal husbandry; animal welfare; bone strength; farming systems; horses; nutrition; pasture; reproduction; surveys